1985
DOI: 10.1161/01.res.57.4.532
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 1-adrenergic and muscarinic cholinergic stimulation of phosphoinositide hydrolysis in adult rat cardiomyocytes.

Abstract: Cardiac alpha-adrenergic receptors mediate cellular responses to norepinephrine through an undefined series of molecular events. We examined the possibility that phosphoinositide hydrolysis was stimulated through alpha-adrenergic receptors in cardiomyocytes purified from adult rat ventricle. Phosphoinositide stores were labeled with [3H]inositol, and [3H]inositol phosphate formation was assessed after the addition of lithium chloride and norepinephrine. Norepinephrine increased the accumulation of [3H]inositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(79 citation statements)
references
References 21 publications
4
74
1
Order By: Relevance
“…Stimulation was not secondary to release of neurotransmitters. Furthermore, Ptlns turnover in heart is not stimulated by increases in cytosolic calcium [2,5], making it unlikely that the response to dilatation is mediated by calcium. While mediation by some other change caused by dilatation cannot be ruled out, it remains possible that 'stretch receptors' can directly activate the Ptlns-(4,5)P2-specific phospholipase C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation was not secondary to release of neurotransmitters. Furthermore, Ptlns turnover in heart is not stimulated by increases in cytosolic calcium [2,5], making it unlikely that the response to dilatation is mediated by calcium. While mediation by some other change caused by dilatation cannot be ruled out, it remains possible that 'stretch receptors' can directly activate the Ptlns-(4,5)P2-specific phospholipase C.…”
Section: Discussionmentioning
confidence: 99%
“…The PtIns turnover pathway has been well studied in many tissues but relatively little detailed information is available for myocardial tissue. In isolated ventricular myocytes [2], ventricle strips [3], perfused ventricles [4] and intact perfused hearts [5], 2-4-fold stimulations by noradrenaline (c~t-receptors) and acetylcholine (muscarinic receptors) have been observed. In the present study isolated perfused rat hearts have been used to study the PtIns turnover response to right atrial distention, a stimulus known to cause release of atrial natriuretic peptide.…”
Section: Introductionmentioning
confidence: 99%
“…In the heart, the most extensively documented biochemical responses to ␣ 1 -adrenergic stimulation is G ␣q activation of phospholipase C (PLC)-mediated hydrolysis of phosphatidylinositol 4,5-bisphosphate, which gives rise to 1,2-diacylglycerol (DAG) and inositol-1,4,5-trisphosphate (IP 3 ), as well as to PKC activation by these second messengers (9,34).…”
mentioning
confidence: 99%
“…In addition to receptors that regulate cyclic AMP (cAMP) formation, there is another type of cell surface receptor which stimulates phospholipase C-mediated hydrolysis of phosphatidylinositol 4,5-bisphosphate (PIP2) into inositol 1,4,5-trisphosphate (IP3) and 1,2-diacylglycerol (DG) [1]. Muscarinic cholinergic and al-adrenergic receptors of the heart are coupled to stimulated polyphosphoinositide turnover [2,3] and it has been suggested that some of the physiological and metabolic effects of adrenergic and cholinergic actions upon myocardium are secondary to receptorCorrespondence address: L. Sterin-Borda, Serrano 665, (1414) Buenos Aires, Argentina mediated hydrolysis of phosphoinositides [1,3]. Furthermore, it has been demonstrated that the products of phospholipase C hydrolysis, namely DG and PI3, may serve as intracellular second messengers.…”
Section: Introductionmentioning
confidence: 99%